Evaluation of annexin A5 as a biomarker for Alzheimer's disease and dementia with lewy bodies - Sohma, Hitoshi; Imai, Shin-ichi; Takei, Norio; Honda, Hirohito; Matsumoto, Kyoichi; Utsumi, Kumiko; Matsuki, Kayo; Hashimoto, Eri; Saito, Toshikazu; Kokai, Yasuo (Frontiers in Aging Neuroscience, 2013)
Background: Alzheimer’s disease (AD) differs from other forms of dementia in its relation to amyloid beta-42. Using a cell culture model we previously identified annexin A5 as an AD biomarker. Plasma level of annexin A5 was significantly higher in AD patients compared to that in control. AD has been identified to share a number of clinical and pathological features with Dementia with Lewy bodies (DLB). The present study was done to examine whether or not plasma annexin A5 is a specific marker for AD, when being compared with the levels of DLB patients. As ApoE gene subtype 4 has been noticed as the probable genetic factor for AD, we also examined and compared ApoE genotype in both AD and DLB. Methods: Blood samples were obtained from 150 patients with AD (aged 77.6 ± 6.5 years), 50 patients of DLB (79.4 ± 5.0) and 279 community-dwelling healthy elderly individuals of comparable age and sex (75.6 ± 8.1). All AD patients met NINCDS-ADRDA criteria and all DLB patients were diagnosed as probable DLB according to the latest consensus diagnostic criteria. Quantification was done using the Chemiluminescent Enzyme Immunoassay Technique using the monoclonal antibodies against annexin A5. DNA genotyping of ApoE was performed by distinguishing unique combinations of Hha1 fragments of PCR-amplified genomic DNA products. Results: The plasma level of annexin A5 was significantly higher in AD patients than in the healthy individuals (control) (P < 0.0001). The plasma annexin A5 level was also significantly higher in DLB patients than in the control group (P < 0.0001). From the ROC curves, the mean areas under the curve were 0.863 and 0.838 for the AD/control and DLB/control, respectively. The rate of ApoE4 carrier status and the frequency of the e4 allele were significantly higher in AD or DLB than in control and there was no significant difference between AD and DLB. Conclusions: These results suggest that both annexin A5 and ApoE4 are common markers for AD and DLB.